2020
DOI: 10.1002/chem.202001227
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Unsymmetrical Cyclopropenimine‐Guanidine Platform for Accessing Strongly Basic Proton Sponges and Boron‐Difluoride Diaminonaphthalene Fluorophores

Abstract: An unsymmetrical guanidine-cyclopropenimine proton sponge DAGUN andt he relatedB F 2-chelate DAGBO are reported. Insight into the structural, electronic, bonding and photophysical properties of these two molecules are presented.J oint experimental and theoretical studies reveal the protonated form of DAGUN possessesa ni ntramolecular N•••HÀNh ydrogen bond which affords ah igh experimental pK BH + of 26.6 (computed = 26.3). Photophysical studies show that in solution DAGUN displays ag reen emission at 534 nm, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…This choice does not imply a priori that the The cyclopropenimine (or cyclopropeneimine, less common name) skeleton (Z: N) has a special status among the heteroatomic analogs of methylenecyclopropene. It is present in many systems, which have been largely studied experimentally and theoretically, in particular in the last ten years, as platforms for developing superbases and organocatalysts [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The imino bond carrying a nitrile group on the nitrogen, >C=N−CN, is present in molecules of biological interest, in particular the neonicotinoids [35][36][37], and in materials developed for their electronic applications [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…This choice does not imply a priori that the The cyclopropenimine (or cyclopropeneimine, less common name) skeleton (Z: N) has a special status among the heteroatomic analogs of methylenecyclopropene. It is present in many systems, which have been largely studied experimentally and theoretically, in particular in the last ten years, as platforms for developing superbases and organocatalysts [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The imino bond carrying a nitrile group on the nitrogen, >C=N−CN, is present in molecules of biological interest, in particular the neonicotinoids [35][36][37], and in materials developed for their electronic applications [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the alcohol moiety of the catalyst activated methyl acrylate via H-bonding, contributing to the high enantioselectivity results [57]. Feng and Liu found that the modified guanidine-amide with 1,2-diphenylethylcarbamoyl and the 2,6-difluorobenzenesulfonamide group was efficient in the asymmetric catalysis [58]. Inspired by the excellent performance of cyclopropenimine in Brønsted base catalysis, we modified the structure of G1 by replacing the guanidine moiety with cyclopropenimine.…”
Section: Design Of New Catalystsmentioning
confidence: 99%
“…According to synthesis investigation on guanidine derivatives with 1,2-diphenylethane-1,2-diamine groups by Feng and Liu [59], and guanidine-cyclopropenimine proton sponges by Dudding [58], we proposed a possible synthesis route for a new catalyst, G4 (Scheme 5). We expected that these results would be helpful for the development for the new catalytic system in the aza-Henry reaction of ketimine.…”
Section: Design Of New Catalystsmentioning
confidence: 99%
“…In point of fact, Breslow in 1957 synthesized the first cyclopropenium ion, namely, triphenylcyclopropenium, while shortly thereafter Yoshida reported an amino-substituted derivative, thus giving rise to tris­(dialkylamino)­cyclopropenium (TDAC) ions or more generally trisaminocyclopropeniums (Figure A). Since, research into the synthesis and properties of amino-substituted cyclopropenium ions has been ongoing and they now find use as catalysts, superbases, ionic liquids, polyelectrolytes and nitrogen-based ligands, platforms for photoelectronic redox-active chemistries, and fluorophores as attested for by our fluorescent cyclopropenium-based proton sponge derivative Janus ( 1 ) , and a boron-containing analog coined DAGBO ( 2 ), among other derivatives (Figure A) . In reflecting upon these various developments, we posited that the coupling of excitation processes, viz, (1) intramolecular charge transfer (ICT, black dotted arrows) from a cyclopropenium core (electron donor, red sphere) to an appended group (electron acceptor, blue sphere), such as an arene ring system and (2) intramolecular through-space conjugation (ITSC, green arrows)a phenomenon observed in organic fluorophoreswould be feasible in trisaminocyclopropenium systems (Figure B).…”
Section: Introductionmentioning
confidence: 97%